Taste masking efficacy of paracetamol alginate beads - Hamed Almuris, Samah; Doolaanea, Abd Almonem (2018)
Many pharmaceutical drugs have unpleasant tastes, most of them being bitter. The problems of bitterness of drugs create a serious challenge to pharmacist especially when the drugs need to be taken by paediatric patients. Paracetamol is one of the common medicines that have a bitter taste. Due to this, taste masking becomes one of the important steps during formulation. Therefore, this study aims to develop a paediatric dosage form of paracetamol through using microencapsulation technique. It is a coating technique that provides a physical barrier around the drug to avoid the drug dissolution into the mouth while keeping the drug bioavailability unchanged. The biopolymer alginate is considered as a good choice for microencapsulation purpose. Alginate is a natural polysaccharide polymer isolated from brown seaweed. There is an increase interest toward the use of alginate gel in the form of beads due to non-toxicity of alginate and their ability to encapsulate drugs under very mild conditions without using high temperatures. Alginate gel beads are prepared by drop-wise of sodium alginate solution into a solution containing divalent metal ion such as calcium ion that leads to the formation of a unique egg box-like gel structure. Furthermore, extra coating of paracetamol-alginate beads with chitosan was increase more taste masking properties. Chitosan is a polysaccharide derived from chitin by alkaline deacetylation. The term of chitosan is used to describe a series of chitosan polymers with different molecular weight, viscosity and degree of acetylation. Chitosan is insoluble in at neutral and alkaline pH values but forms salt with inorganic and organic acid. in-vitro dissolution testing was used to evaluate taste masking capability, by quantifying release in simulated oral cavity conditions. From in-vitro studies, it can be concluded that the paracetamol alginate beads able to mask the bitter taste of paracetamol.